AlScN Film Based Piezoelectric Micromechanical Ultrasonic Transducer for an Extended Long-Range Detection - Haolin Yang; Meilin Ji; Xueying Xiu; Haochen Lv; Alex Gu; Songsong Zhang (Micromachines, 2022)
Piezoelectric micromachined ultrasonic transducers (PMUTs) have been widely applied in distance sensing. However, the sensing distance of currently reported miniaturized ultrasonic sensors (e.g., PMUTs or CMUT) is still limited up to a certain range (e.g., ≤5 m) compared to conventional bulk ultrasonic devices. This paper reports a PMUT array design using scandium-doped aluminum nitride (AlScN) as its piezoelectric layer for an extended long-range detection purpose. To minimize air attenuation, our device is resonating at 66 kHz for a high receive sensitivity of 5.7 mV/Pa. The proposed PMUT array can generate a sound pressure level (SPL) as high as 120 dB at a distance of 10 cm without beam forming. This PMUT design is catered for a pin-to-pin replacement of the current commercial bulk ultrasonic ranging sensor and works directly with the conventional range finding system (e.g., TI PGA460). In comparison with the common bulk transducer, the size of our device is 80% smaller. With the identical ranging detection setup, the proposed PMUT array improves the system SNR by more than 5 dB even at a distance as far as 6.8 m. The result of extended sensing distance validates our miniaturized PMUT array as the optimized candidate for most ultrasonic ranging applications. With the progressive development of piezoelectric MEMS, we believe that the PMUT technology could be a game changer in future long-range sensing applications.